Pembentukan Nilai Karakter Mulia Perspektif Hadis - Hikmatul Luthfi; Arif Amarullah Ibrahim; Nuroh (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2024)
Noble character is the foundation of a healthy and well-functioning society. In the context of Islam, noble character is not only considered an important aspect of a Muslim’s personal life but also a vital component that determines the quality of social interactions and the community as a whole. This research uses a descriptive qualitative method with a thematic study of hadith and library research. The aim of the research is to identify the related hadiths and understand how noble character is applied in daily life. The results and discussion indicate that the values and formation of noble character in Islam consist of honesty, patience, generosity, and social responsibility. In daily life, honesty, patience, and generosity are often practiced. For instance, giving charity (sadaqah) is a form of generosity, and patience is exhibited by remaining patient and grateful when faced with adversity.